2020
DOI: 10.3390/pharmacy8020089
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Community Pharmacists in the Detection of Clinically Relevant Drug-Related Problems in Chronic Kidney Disease Patients

Abstract: Community pharmacists (CPs) have traditionally had limited access to patients’ estimated glomerular filtration rate (eGFR) during the medication-dispensing process. The increasing access to shared electronic health records is making eGFR available, but the skills needed to detect and manage clinically relevant drug-related problems (DRPs) are poorly documented. The primary objective of this study was to investigate the role of CPs in the medication-dispensation process for elderly patients with renal impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…Nevertheless, this problem should decrease with the emergence of computerized discharge orders. The frequencies of the two main DRPs showed no significant difference according to the setting and are in agreement with those reported in previous studies [ 5 , 11 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, this problem should decrease with the emergence of computerized discharge orders. The frequencies of the two main DRPs showed no significant difference according to the setting and are in agreement with those reported in previous studies [ 5 , 11 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…This is also confirmed by the literature, since several studies have suggested positive effects (e.g. increased detection of DRPs [42]) on clinical (e.g. blood pressure, haemoglobin, parathyroid hormone, and creatinine clearance), humanistic (e.g.…”
Section: Discussionsupporting
confidence: 81%
“…blood pressure, haemoglobin, parathyroid hormone, and creatinine clearance), humanistic (e.g. health-related quality of life, patient satisfaction) and economic outcomes when information on renal function was available to pharmacists [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, since MRPs are very common in patients with CKD, identification, prevention, and management would 15, 16 require competency and an interdisciplinary approach . Identifying, resolving actual, and preventing potential MRPs is a major role pharmacist in community and hospital [17][18][19] practice have assumed with the consent of clinicians . MRPs unidentified and unresolved in CKD have a negative impact on desired patient and therapeutic outcomes resulting in reduced quality of life, increased hospital-stay, increased overall healthcare cost and even increasing the 20, 21 risk of morbidity and mortality…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%